Kicking & screaming - Dylan, Jesse; Ferrell, Will, 1967-; Duvall, Robert; Ditka, Mike.; Walsh, Kate, 1967-; Vander, Musetta, 1969-; Ahern, Lloyd; Thorin, Donald E., 1930-; Isham, Mark.; Universal Studios Home Video (Firm) ([Universal City, Calif.] : Universal Studios Home Entertainment, 2005)
Family man Phil Weston, a lifelong victim of his father's competitive nature, takes on the coaching duties of a kids' soccer team, and soon finds that he's also taking on his father's dysfunctional way of relating to others.
Title from container.
Special features: The red cards, deleted scenes; the yellow cards, outtakes; alternate takes; from Rome to Hollywood; kickin' it with the kids; soccer camp; behind the net, the making of Kicking & screaming.
Cinematographers, Lloyd Ahern II, Donald E. Thorin ; editors, William Kerr, Stuart H. Pappé, Peter Teschner ; music, Mark Isham ; costume designer, Pamela Withers-Chilton ; production designer, Clayton Hartley.
Will Ferrell, Robert Duvall, Mike Ditka, Kate Walsh, Musetta Vander, Dylan McLaughlin, Josh Hutcherson, Steven Anthony Lawrence, Jeremy Bergman, Elliott Cho.
MPAA rating: PG; thematic elements, language and some crude humor.
DVD, 1.33:1 presentation; Dolby Digital 5.1 surround.
Keywords: Competition (Psychology) -- Drama; Soccer coaches -- Drama; Soccer -- Drama; Comedy films